Prediksi Penyakit Diabetes Dengan Naive Bayes - Wardana, Yuni; Sari, Devni Prima (UNIVERSITAS NEGERI PADANG, 2023)
Diabetes is one of the top ranked diseases for non-communicable diseases which is top cause of death worldwide. Every year 442 million people worldwide have diabetes and 1.6 million people die due to diabetes. With increasing cases of diabetes every year, this detection may need to be done before diabetes occurs. So a research was conducted on diabetes prediction using the Naïve Bayes method. According to the Naïve Bayes model, people with diabetes have a 28% chance of developing diabetes and a 72% chance of not having diabetes. And this research achieved 94% accuracy, 95% precision, and 98% recall.